Synthesis, Biological Evaluation, and Modeling of Dimeric PPI Analogues as Novel DNA Minor Groove Binders - Mao-Sheng Cheng (Molecules, 2008)
A series of symmetrical dimeric proton pump inhibitor (PPI) analogues, designed as novel type DNA minor groove binders, was synthesized and evaluated for anti-tumor activity. Some of these new compounds showed IC50 values below 10 ÃŽÂ¼M in an in vitro anti-tumor test. A molecular modeling study was performed to confirm the sequence selectivity of these compounds towards AT base pairs in DNA. Two effective compounds were selected and docked into the minor groove of DNA. The snug binding may be responsible for their cytotoxic and anti-tumor effects.